Granitoids Aquifer Water Quality Appraisal in Kassena Nankana, Bawku West, and Garu Tempane Districts in Ghana (Global Journal of Science Frontier Research, 2025)
The most valuable natural resource on Earth is groundwater which serves more than two billion populaces as a drinking water source worldwide Despite its vital importance groundwater has faced significant challenges particularly in terms of its quality Therefore a thorough understanding of groundwater hydrogeochemistry is essential to assess the water needs for domestic use and irrigation use This research evaluates groundwater quality in granitoid aquifers in the Kassena Nankana Bawku West and Garu Tempane districts of Ghana An integrated approach was used incorporating The World Health Organization WHO the Water Quality Index WQI and irrigation indices to offer recommended values for domestic and irrigation purposes The study utilized a total of 121 groundwater quality reports obtained from the research area s many boreholes The integrated findings based on the WHO guideline values WQI and irrigation indices indicate that nearly 100 of the researched area s groundwater has splendid drinking water quality while 92 is suitable for irrigation An extensive groundwater quality evaluation has been conducted in the study area offering valuable information that can contribute to the studied area s groundwater management and development sustainably
Keywords: appraisal; aquifers; ghana; granitoid; irrigation indices; water quality index